Od dialogu do transgresji - Tokarz, Bożena (Przestrzenie Teorii, 2008)
The attitude of dialogue meant candour and creativity in the history of European cultures and literatures. It was reflected in the specific philosophical conceptions, in the alternative worlds which were brought to life, in the literary forms and in the art of creation. Its remarkable activation which took place in the 20th century is one of the characteristic features of that epoch. Dialogism denotes an interactive structure with a variable dominant considering the replicated side and the replicating one which participate in the dominant. They are submitted to constant semiosis. Aiming at agreement, dramatic tensions which arise as a consequence of the presence of the two sides may be reduced in accordance with the logic of acquiescence or retained in the perspective of the logic of contradictions. The conflict between agreement and selfunderstanding constitutes the drama which is the basis of all existence. It is transcended by the art - consequently by literature - in the transgressional processes, relativizing its own boundaries: ontological, aesthetic, structural and communication.